Effect of enriched biochar based fertilizers on growth, yield and nitrogen use efficiency in direct-seeded rice (Oryza sativa) - ROY, ARKAPRAVA; PYNE, SUHITA; CHATURVEDI, SUMIT (The Indian Journal of Agricultural Sciences, 2021)
A field experiment was conducted at Norman E. Borlaug Crop Research Centre, G. B. Pant University of Agriculture and Technology, Pantnagar, Uttarakhand during kharif (rainy) 2018 to assess effect of enriched biochar (EB) based fertilizers on crop growth, productivity and nutrients use efficiency in direct seeded rice (DSR). Enriched biochar based fertilizers i.e. Enriched biochar-1 (EB-1), Enriched biochar-2 (EB-2), Urea enriched biochar-1 (UEB-1) and Urea enriched biochar-1(UEB-2) were prepared and characterized at IFS laboratory, GBPUA&T, Pantnagar.The experiment was laid out in randomized block design with eight treatments i.e. 100% Recommended dose of fertilizer (RDF) through conventional fertilizers, 75, 100 and 125% RDF through enriched biochar based fertilizers EB-1+UEB-1 and EB-2+UEB-2 and no fertilizer application as control replicated thrice. Highest growth, yield parameters and yield of DSR were recorded under application of EB-2+UEB-2 at 125% fertility level. Application of EB-2+UEB-2 at 100% fertility level also gave at par yield with its application at 125% fertility level and significantly higher yield (13.5%) as compared to application of conventional fertilizers at similar fertility level. Application of both the EB fertilizers at 75% fertility level resulted in at par yield with application of 100% fertility level through conventional fertilizers. Nitrogen uptake by grain and straw were significantly higher under application of EB-2+UEB-2 at 125% fertility level. However, among these EB fertilizers, application of 100% RDF through EB-2+UEB-2 resulted in 30.70% and 29.50% more agronomic efficiency (AE) and apparent nitrogen recovery (ANR), respectively as compared to application of conventional fertilizers.